Polyphenols isolated from lychee seed inhibit Alzheimer's disease-associated Tau through improving insulin resistance via the IRS-1/PI3K/Akt/GSK-3β pathway. (6th April 2020) - Xiong, Rui; Wang, Xiu-Ling; Wu, Jian-Ming; Tang, Yong; Qiu, Wen-Qiao; Shen, Xin; Teng, Jin-Feng; Pan, Rong; Zhao, Ya; Yu, Lu; Liu, Jian; Chen, Hai-Xia; et al.
Abstract: Ethnopharmacological relevance: Lychee seed, the seed of Litchi chinensis Sonn. is one of the commonly used in traditional Chinese medicine (TCM). It possesses many pharmacological effects such as blood glucose and lipid-lowering effects, liver protection, and antioxidation. Our preliminary studies have proven that an active fraction derived from lychee seed (LSF) can significantly decrease the blood glucose level, inhibit amyloid-β (Aβ) fibril formation and Tau hyperphosphorylation, and improve the cognitive function and behavior of Alzheimer's disease (AD) model rats. Aim of the study: The aim of this study was to identify the main active components in LSF that can inhibit the hyperphosphorylation of Tau through improving insulin resistance (IR) in dexamethasone (DXM)-induced HepG2 and HT22 cells. Materials and methods: The isolation was guided by the bioactivity evaluation of the improvement effect of IR in HepG2 and HT22 cells. The mRNA and protein expressions of IRS-1, PI3K, Akt, GSK-3β, and Tau were measured by RT-PCR, Western blotting, and immunofluorescence methods, respectively. Results: After extraction, isolation, and elucidation using chromatography and spectrum technologies, three polyphenols including catechin, procyanidin A1 and procyanidin A2 were identified from fractions 3, 5, and 9 derived from LSF. These polyphenols inhibit hyperphosphorylated Tau via the up-regulation of IRS-1/PI3K/Akt and down-regulation of GSK-3β. Molecular docking result further demonstrate that these polyphenols exhibit good binding property with insulin receptor. Conclusions: catechin, procyanidin A1, and procyanidin A2 are the main components in LSF that inhibit Tau hyperphosphorylation through improving IR via the IRS-1/PI3K/Akt/GSK-3β pathway. Therefore, the findings in the current study provide novel insight into the anti-AD mechanism of the components in LSF derived from lychee seed, which is valuable for the further development of a novel drug or nutrient supplement for the prevention and treatment of AD. Graphical abstract: Image 1